Cultural diversity in the workforce: the tension between creativity and conflict - Williamson, Stephanie (2008)
Globalisation of the modern business, changing demographics and the rapid growth of multinational firms has meant that managing cultural diversity in organisations is more important today than ever before. Whilst the existence of a culturally diverse workforce can increase an organisations' competitiveness, by providing creative ideas and solutions, it can also be detrimental to overall performance, given the issues of conflict that may arise. The multicultural challenge, therefore, revolves around how effectively organisations can manage this tension between conflict and creativity in order to create a lasting source of competitive advantage. Based on information gathered from 12 interviews with employees from Hong Kong based firms, this study examines ways in which managers can successfully address the tension between creativity and conflict in a culturally diverse workforce. The results indicate that key steps a manager can take to achieve a harmonious, creative and productive workforce include the following: cultivating an open and trusting relationship with employees; acting as an example and role model for the rest of the workforce to follow, and resolving conflicts in a prompt and fair manner. In addition to this, organisations must develop and maintain a corporate culture that promotes core values such as openess, trust, communication and understanding. Importantly, organisations must also undertake a rigorous and thorough recruitment process. This study affirms that, when managed effectively, a multicultural workforce can serve to greatly enhance overall organisational performance.